Profiling students’ environmental care attitudes taught using Sasak Tribe local wisdom-integrated model - H. Hunaepi; Ika Nuraini Dewi; S. Sumarjan (University of Muhammadiyah Malang, 2019)
Sasak Tribe possesses unique local wisdom which is potential to be utilized in term of improving students' care attitudes toward the environment. This study aimed at profiling students' evironmental attitudes who were taught using Sasak Tribe local wisdom-integrated model. This descriptive research was designed with a one-shot case study. The sample used in this study was 140 VII graders chosen using random sampling technique. The sample comprised of 3 classes of SMPN 2 Gunung Sari and 3 classes of SMPN 3 Lingsar placed in West Nusa Tenggara-Indonesia. The data analysis technique used was descriptive statistics in term of central tendency. The measured indicators were environmental awareness (EA), developing empathy (DE), and effect handling (EH). The results showed that the students live in suburb area tended to have better environmental care attitudes, in which the mean values were 86.66 (EA), 75.69 (DE), and 42.66 (EH) compared to those who live in urban area in which the mean values were 68.73 (EA), 57.07 (DE), and 30.62 (EH). Based on this findings, further evaluation in several aspects should be done.